Implementasi Program Keagamaan dalam Membentuk Budaya Religius Peserta Didik di MTs Ma’arif Sidomukti Kebomas Gresik - Dewi Mashitho; Syifa Rizqina Aulia Putri (Prodi PAI STIT Raden Santri Gresik, 2025)
The implementation of religious programs is an effort by madrasas to overcome moral and spiritual crises among students. This crisis is characterized by a decline in religious values, a lack of awareness of worship, and an increase in juvenile delinquency, which is a direct result of external negative influences such as social media and the unequal focus of education on the cognitive aspect alone. This condition is designed to encourage self-improvement, ensure the consistency of worship, and instill moral values in each individual. This study aims to analyze the implementation of religious programs and the results of religious programs in shaping the religious culture of students at MTs Ma'arif Sidomukti. In the study, a qualitative method with a descriptive approach was used. This is to describe and disclose data on the implementation of religious programs in shaping the religious culture of students at MTs Ma'arif Sidomukti Kebomas Gresik. This research produces various aspects of research, namely the planning, implementation, and evaluation stages. The forms of religious programs that are applied include congregational prayers, the habit of reading asmaul husna, the habit of reading aqidatul awwam, mukhadoroh, the recitation of reading short letters, tahlil, surah yasin, surah al-waqiah, surah al-mulk, princess, ishari, pilgrimage visit waliyullah, istighosah dzikrudz dzakirin, shodaqoh sedino sewu (S3), and also Friday morning infaq (INJAGI). It has an impact on students by forming a religious culture which can be seen from increasing worship discipline, confidence, tolerance, and polite and noble behavior among students, and also exploring the potential in students who have the motivation to excel and be competitive. Based on the results of this study, it proves that the implementation of religious programs can significantly shape the religious culture of students in Madrasahs. This research is expected to make a positive contribution to religious programs and become a provision for sustainable living for students in the community.